2016
DOI: 10.3390/info8010002
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries in Genetic Systems and the Concept of Geno-Logical Coding

Abstract: Abstract:The genetic code of amino acid sequences in proteins does not allow understanding and modeling of inherited processes such as inborn coordinated motions of living bodies, innate principles of sensory information processing, quasi-holographic properties, etc. To be able to model these phenomena, the concept of geno-logical coding, which is connected with logical functions and Boolean algebra, is put forward. The article describes basic pieces of evidence in favor of the existence of the geno-logical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This will promote the inclusion of genetics and all biology in the field of profound mathematical natural science. Consideration of biological phenomena, including the phenomena of inheritance of the intellectual abilities of biological bodies, from the standpoint of the theory of quantum computers, gives many valuable opportunities for their comprehension and also for development of artificial intelligence systems [Petoukhov, 2016a,b;Petoukhov, Petukhova, 2017a; (the work [Biamonte et al, 2017] contains a review about quantum computing and the problems of artificial intelligence). For example, an adult human organism has around 10 trillion (10 14 ) human cells and each of cells containts an identical complect of DNA, whose genetic information is used for physiological functioning organism as the holistic system of cells.…”
Section: Some Concluding Remarksmentioning
confidence: 99%
“…This will promote the inclusion of genetics and all biology in the field of profound mathematical natural science. Consideration of biological phenomena, including the phenomena of inheritance of the intellectual abilities of biological bodies, from the standpoint of the theory of quantum computers, gives many valuable opportunities for their comprehension and also for development of artificial intelligence systems [Petoukhov, 2016a,b;Petoukhov, Petukhova, 2017a; (the work [Biamonte et al, 2017] contains a review about quantum computing and the problems of artificial intelligence). For example, an adult human organism has around 10 trillion (10 14 ) human cells and each of cells containts an identical complect of DNA, whose genetic information is used for physiological functioning organism as the holistic system of cells.…”
Section: Some Concluding Remarksmentioning
confidence: 99%
“…The discovery of new binary fractal-like patterns, which are revealed from long genetic sequences by means of this method, provokes many questions about relationship between the genetic system and those fields of science and technology where digital binary fractals are used, for example the fields of fractals in radiophysics, technology of fractal antenna, and fractal codes. In our opinion, the described results are useful for the bio-mathematical concept of geno-logical coding [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Its appropriate decimal meanings are 22 and 14. In such way, this 5-mer ATGGC can be represented not only as the appropriate cell with coordinates (22,14) inside the genomatrix [A G; C T] (5) but also as the point with decimal coordinates (22,14) in the orthogonal Cartesian system of coordinates (x, y). Taking into account the chosen connection ( Figure 2) between each sub-alphabet and one of the X, Y, Z axes of the Cartesian system of coordinates, the following correspondence exists between Kronecker families of genomatrices and 2-dimensional planes (x, y), (x, z) and (y, z) of the Cartesian system: …”
Section: Matrix Representations Of Whole Sets Of N-plets (Or N-mers)mentioning
confidence: 99%
See 1 more Smart Citation
“…But the notion of recurrence sequences of numbers can be generalized to a notion of recurrence sequences of matrices including tensor recurrence sequences of matrices. The author's studies of the systems of the alphabets of the molecular genetic system showed that their structural features are associated with tensor recurrence sequences of matrices, for example, [C, A; T, G] n , or [G, T; C, A] (n) where n = 1, 2, 3,… The systematic analysis of these tensor recurrence sequences, proposed and carried out by the author since 2008, has led to many meaningful results about the hidden relationship of genetic and physiological subsystems, as described in many publications, for example, [Petoukhov, 2008[Petoukhov, , 2011[Petoukhov, , 2012[Petoukhov, , 2016[Petoukhov, , 2017[Petoukhov, -2019[Petoukhov, , 2020aPetoukhov, He, 2010;Petoukhov, Petukhova, 2017;Petoukhov, Petukhova, Sirin, 2019;Petoukhov, Tolokonnikov, 2020].…”
Section: Recurrence Sequences Of Genetic Matricesmentioning
confidence: 99%